Uric acid is associated with long-term adverse cardiovascular outcomes in patients with acute coronary syndrome undergoing percutaneous coronary intervention. (March 2018) - Tscharre, Maximilian; Herman, Robert; Rohla, Miklos; Hauser, Christina; Farhan, Serdar; Freynhofer, Matthias K.; Huber, Kurt; Weiss, Thomas W.
Abstract: Background and aims: Evidence links uric acid (UA) with the promotion of cardiovascular disease. We assessed the prognostic value of UA on long-term major adverse outcomes (MACE) in patients with acute coronary syndrome (ACS), undergoing percutaneous coronary intervention (PCI). Methods: As primary endpoint, we assessed the association of UA (continuous and dichotomized) with MACE, including cardiovascular death, myocardial infarction (MI) and stroke, using Cox regression and propensity matching. As secondary endpoints, the influence of hyperuricemia (defined as UA levels > 6.0 mg/dl in women, and >7.0 mg/dl in men) was analysed separately for cardiovascular death, MI, and stroke. The incremental prognostic value of UA was tested using the net reclassification improvement (NRI), and the integrated discrimination improvement (IDI). Results: We included 1215 patients. Hyperuricemia was present in 356 (29.3%) patients. Mean follow-up was 5.5 years. UA (HR 1.091 [1.035–1.150]; p  = 0.001) and hyperuricemia (HR 1.750 [1.388–2.207]; p  < 0.001) were significantly associated with MACE. Results were consistent between Cox regression and propensity matched analysis. Patients with hyperuricemia had a 1.6-fold increased relative risk for cardiovascular death ( p  = 0.005) and a 1.5-fold increased risk for MI ( p  = 0.032). For stroke, hyperuricemia only constituted a confounder (HR 1.104; p  = 0.970). The prognostic accuracy of an established risk prediction model was significantly increased by adding UA (continuous NRI p  = 0.004; categorical NRI p  = 0.029; IDI p  = 0.002). Conclusions: Our data suggest an independent association of elevated UA with long-term MACE in ACS patients undergoing PCI. Whether lowering UA might be beneficial remains to be elucidated in large clinical trials. Highlights: Data on uric acid and adverse long-term outcome in patients with ACS is scarce. 1215 ACS patients with a mean follow-up of 5.5 years were included. Hyperuricemia was associated with a 1.7-fold increased risk for MACE. Hyperuricemia was associated with a 1.6-fold risk for cardiovascular-death and with a 1.5-fold risk for MI. Uric acid significantly increased the prognostic accuracy of an established risk prediction model.